Variability of pod and seed traits on candidate plus tree Pongamia pinnata in Indonesia - Danu; Hani Sitti Nuroniah; Deddy Dwi Nur Cahyono; Aam Aminah; Dida Syamsuwida; Nurmawati Siregar; Eliya Suita; Dharmawati Djam’an; Abdul Hakim Lukman; Kresno Agus Hendarto (Forest Science and Technology, 2024)
Pongamia pinnata is a species native to Indonesia and a potential bioenergy species to be developed on marginal land in Indonesia. This study examined variability in the pods, seeds, and oil content of 44 candidate plus trees (CPT) collected from a natural distribution of pongams on three islands and pongam domestication plots. The measurements of the phenotypic properties of the pods and seeds were recorded (length, width, thickness, and weight), as well as the oil content of the seeds. This study showed that Pongamia pinnata in Indonesia has variable pod and seed traits. However, there was no significant correlation between the pods/seeds trait with the oil content, indicating that the size of the seed does not determine oil content. The narrow-sense heritability of seed weight and oil content were high. The cluster of 44 CPT referred to oil content and 17 CPT can be promoted for breeding program. This study will help better identify for tree selection in a pongam breeding program.